Analysis of Monitoring and Evaluation Practices on Performance of Non-Governmental Organizations’ Project in Kiambu County, Kenya - Njiru, Moses; Thoronjo, Erastus (PT. Riset Press International, 2024)
Monitoring and evaluation is an essential practice in project management as it helps the project's scope to be defined, interventions to be established, and project managers to have an understanding of how project interventions would affect the project's implementation and objectives. The purpose for this study was to analyze monitoring and evaluation practices on the performance of Non-Governmental Organizations (NGOs) in Kiambu County in Kenya. The three main research objectives of this research are; the monitoring and evaluation planning practice; the monitoring and evaluation technical skills practice, and the participatory monitoring and evaluation practice on the performance of NGO’s in Kiambu County. This study utilized a descriptive investigative approach, with a sample size of 210 being non-governmental employees drawn from; Monitoring and evaluation officers, Project managers, and Stakeholder representatives out of a target population of 441. The tool for data analysis was the statistical package for social science version 26 and the results obtained were presented using tables and figures. The results of regression evaluation of monitoring and evaluation depicted a very strong connection between monitoring and evaluation planning practice and non-governmental organizations' project performance. The results of monitoring and evaluation of technical skill illustrated a positive connection between monitoring and evaluation of technical skill practice and non-governmental organizations' project performance. Further, the findings on Participatory monitoring and evaluation represented a confident connection between Participatory monitoring and evaluation practice and non-governmental organizations' project performance. Regression analysis results indicated that monitoring and evaluation planning practice; the monitoring and evaluation technical skills practice, and the participatory monitoring and evaluation practice positively and significantly impact the project performance of non-governmental organizational In Kiambu County, Kenya. This study therefore concluded that monitoring and evaluation planning practice; the monitoring and evaluation technical skills practice, and the participatory monitoring and evaluation practice positively and significantly impact the project performance of non-governmental organizational In Kiambu County, Kenya. This study recommends non-governmental organizational In Kiambu County, Kenya to pay particular attention to participatory monitoring and evaluation practice by focusing on those strategies that embrace participatory approaches, to create more inclusive and impactful M&E processes that contribute to sustainable development and positive change within communities. The findings in this research study will benefit, scholars, M&E practitioners, programme managers, government institutions, project stakeholders, and donor community in proper integration of the monitoring and evaluation practices for project performance.